1974
DOI: 10.1159/000224940
|View full text |Cite
|
Sign up to set email alerts
|

Second Messenger System in Neoplasia

Abstract: Hormones have been observed to initiate tumors in animals and are thought to be involved in cellular selection and/or progression of neoplastic lesions in humans. Hormones are the ‘First messengers’ in mammalian systems as they allow cell to cell and organ to organ communication A ‘second messenger’ system is currently being elucidated. This second messenger system involves several cellular membraneous and intracellular components which act to relay extracellular messages to intracellular targets including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 147 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…The overall effect on growth may de pend on the intracellular ratio of cAMP to cGMP le vels: a high cAMP/cGMP ratio may inhibit cell growth and a low ratio may stimulate cell growth [1]. For example, if 20% serum is added to cultures of quiescent Balb/3T3 cells, growth stimulation results and the cGMP level transiently rises at the same time that the cAMP level transiently drops (34], Also, the addition of cGMP or its analogs was shown to induce DNA syn thesis in quiescent Balb/3T3, BHK or Swiss 3T3/4A cell cultures [34], Treatment with cAMP has been reported to de crease cellular protein synthesis and RNA synthesis in normal Balb/c spleen cell cultures, and also to de crease the level of mitogen-induced protein and RNA synthesis in these cells [33], By contrast cGMP has been reported to stimulate protein synthesis in quies cent fibroblast cells [34], We found that theophylline treatment (IQ-3 M) of B-16 cells did not result in in hibition of protein synthesis, although significant inhi bition was seen at a 10-2 M concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall effect on growth may de pend on the intracellular ratio of cAMP to cGMP le vels: a high cAMP/cGMP ratio may inhibit cell growth and a low ratio may stimulate cell growth [1]. For example, if 20% serum is added to cultures of quiescent Balb/3T3 cells, growth stimulation results and the cGMP level transiently rises at the same time that the cAMP level transiently drops (34], Also, the addition of cGMP or its analogs was shown to induce DNA syn thesis in quiescent Balb/3T3, BHK or Swiss 3T3/4A cell cultures [34], Treatment with cAMP has been reported to de crease cellular protein synthesis and RNA synthesis in normal Balb/c spleen cell cultures, and also to de crease the level of mitogen-induced protein and RNA synthesis in these cells [33], By contrast cGMP has been reported to stimulate protein synthesis in quies cent fibroblast cells [34], We found that theophylline treatment (IQ-3 M) of B-16 cells did not result in in hibition of protein synthesis, although significant inhi bition was seen at a 10-2 M concentration.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP acts as the intra cellular '2nd messenger' for many hormones, and also appears to be intimately involved in the regulation of cell growth, metabolism, and differentiated cell func tions (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in cyclic nucleotide metabolism in many animal and human malignancies have been reported (Criss, 1974;Ryan & Heidrick, 1974;Hunt & Martin, 1980). It has been suggested that such changes are determinants of the abnormal growth of tumours, but the evidence from studies in oivo usually does not support this (Hunt & Martin, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…dB-cAMP also prevents the induction of DNA synthesis induced by adenovirus type 12 in BHK cells arrested in G-1 (57) and reduces the tumorigenicity of Celovirus transformed CHO cells (24). Adenyl cyclase, the enzyme which catalyzes the synthesis of 3':5'-cyclic AMP from ATP, is part of the plasma membrane (58).…”
mentioning
confidence: 99%
“…Its activity can be modified by extracellular agents which bind to plasma membrane receptors (58)(59)(60). Insulin, which affects adenyl cyclase, can t be immobilized on Sepharose beads and still retain its effectiveness even though it cannot enter the cell.…”
mentioning
confidence: 99%